The influence of edge treatment on fatigue behavior of thermal cut edges - Grimm, Jan-Hendrik; Dinize Castro, Juliana; von Selle, Hubertus; Braun, Moritz; von Bock und Polach, Rüdiger Ulrich Franz; Ehlers, Sören; Hensel, Jonas; Hesse, Ann Christin; Dilger, Klaus (American Society of Mechanical Engineers, 2022)
Thermal cut edges can be found in most maritime structures, e.g. in window openings or hatch corners on ships. It is very common to treat free plate edges by grinding or sandblasting due to fatigue and coating requirements. The aim of this study is to review the fatigue behavior of typical treatment methods. Within this study several fatigue tests are performed to outline the influence of treatment methods used for different steel grades, plate thicknesses and cutting processes. Especially the influence of the local edge geometry caused by treatment like grinding or milling is not covered by fatigue rules and guidelines like Eurocode or IIW. Also, the influence of yield strength is not considered by these regulations. Only in shipbuilding a fatigue bonus for high strength steels is given. However, these rules are based on older data and an update is requested by ship building industries. For the investigation shipyards and partners from other industries produced a big number of specimens for fatigue tests. Steel grades are from S235 to S460. Surface roughness as well as local treatment geometry are well documented. In addition, hardness as well as residual stress measurements were performed. Finally fatigue tests were done. Overall goal of the study is to present applicable FAT curves to be used for fatigue assessment.